PENGARUH KONSENTRASI ABU VULKANIK TERHADAP KUALITAS AIR DAN SINTASAN LELE (Clarias sp.) - , BESTARI IBNU R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research used Completely Randomized Design with experimental method consisted of 5 volcanic ash concentrations and each of treatment has triplicate. Volcanic ash concentrations consisted of 0, 50, 100, 150 and 200 g/L. Volcanic ash was taken in Cangkringan District, Sleman Regency on September 2012 (the eruption of Merapi Mount was became on November 2010). It was filtered with sifter mesh size 500 Î¼m. The research has been done to know the water quality, survival and growth of catfish which cultured and subjected to volcanic ash concentrations. Catfish seeds (8-12 cm) were cultured 56 days on fiber tank (dimension 48x29x29 cm3 and water volume 25 L) with the density 10 fishes/tank (72 fishes/m2). The result showed that the difference of volcanic ash concentrations were not significantly on water temperature, conductivity, Total Dissolved Solid (TDS), Total Suspended Solid (TSS), pH, dissolved oxygen, free carbon dioxide, alkalinity, hardness, sulfate and ammonia, however significantly on water transparency, water turbidity, survival and absolute weight growth of fish. The more high volcanic ash concentration caused water transparency decreased, water turbidity increased, survival and absolute weight growth of fish decreased. Catfish was still good cultured on volcanic ash concentration until 100 g/L.